Violations of Language in Learning Process at Toraja Christian University of Indonesia - Resnita Dewi; Simon Rukuk (STAI Hubbulwathan Duri, 2022)
Lecturers and students as academics are required to be polite not only in behaving, but also in language. But in reality, often we find lecturers and students who do not show such courtesy, especially in the language or often called violations of language courtesy. This research aims to reveal violations of language courtesy committed by the academic community of Toraja Christian University of Indonesia (UKI Toraja), specifically in the learning process. Through this research, it is expected that various forms of violations of language courtesy can be expressed. Research on the violation of language courtesy is a type of qualitative descriptive research. This research was conducted at UKI Toraja specifically in the Indonesian Language education and Satra study program. The data in this study is the use of language used by lecturers and students of UKI Toraja in the learning process, both orally and in writing. Data is collected with documentation, record, and record techniques. The data was further analyzed using sociopragmatic approaches, which are approaches used to express the meaning of language externally. The results showed violations of language courtesy in the learning process at UKI Toraja were expressed through violations of wisdom maxims, violations of generosity, violations of reward maxims, violations of match maxims, and violations of simplicity maxims.